Influences of Micro-Teaching in Developing the Time Management Skill In Teaching Process. (A study based on the teachers of Vavuniya Gamini National School) - Douglas, S. (Pasdunrata National College of Education, Sri Lanka, 2018)
Micro- teaching is one of the best techniques which can be used to develop the specific skills of the teacher students. Time management is the most prominent challenge faced by most of the teachers in initial professional stage and it would be perfectly developed through experience. The purpose of this study is to find out how far does the micro-teaching influence developing the time management skill of the prospective teachers in the initial stage of the profession? The study was conducted in Gamini National School in Vavuniya District along with ten National Diploma in Teaching holders (Experimental group) and ten Graduates (Control Group). The study period was the first month of the teaching profession. Data was collected by administering questionnaires followed by semi structured interviews and classroom observations. The collected data were analyzed using qualitative and quantitative methods. The findings clearly show that the micro-teaching had facilitated the National Diploma holders in planning the time in the classroom. The teaching process was observed with the lesson plan in order to get the most reliable result. The class room observation showed two third of the National Diploma Holders managed the time from the very first week much effectively. Whereas with the Graduates it was only one third. In the semi structured interview sixty-six percentage of the teachers agreed that the micro-teaching provides the ground for developing many skills such as time management, presenting the lesson and moulding the behavior. The findings of this study will make the teacher educators as well as the teacher students to feel confident while practicing micro-teaching. Further the study emphasizes micro-teaching influences positively the student teachers in developing the time management skill in the initial stage of the profession.
Keywords: Micro-teaching; Time Management; Teaching Skills; Student teachers; Teacher; Training